ANALISIS POTENSI PELANGGARAN HAM DALAM KASUS PENYELUNDUPAN KAYU (ILLEGAL LOGGING): PERSPEKTIF POLITIK HUKUM DAN IMPLIKASINYA TERHADAP KEBERLANJUTAN LINGKUNGAN - Asep Mahbub Junaedi; Nurhayati, Nasruddin, Yusuf Setyadi, Sugianto (JOURNAL OF LAW AND NATION, 2025)
This study aims to analyze the potential human rights violations in cases of illegal logging from the perspective of legal politics and their implications for environmental sustainability. Illegal logging not only threatens forest ecosystems as vital resources but also has the potential to violate fundamental human rights, such as the right to a healthy environment and a decent livelihood. Using a normative-juridical approach, this research examines the existing legal framework, weaknesses in law enforcement, and political dynamics influencing natural resource management. The findings reveal that weak law enforcement and certain political interests facilitate illegal logging practices, resulting in environmental degradation and the violation of local communities’ rights, particularly vulnerable groups like indigenous peoples. This study recommends strengthening regulations, enforcing strict sanctions, and ensuring sustainable monitoring to protect human rights and promote environmental sustainability